Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 234732544 species occurrences available in GBIF matching the query: { "Year" : [ "1974-2000" ] } The dataset includes 234732544 records from 14255 constituent datasets: 43 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 34 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 2 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 226603 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 8 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 1 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 269 records from Range table from benthic foraminifers in ODP Hole 161-974B. 3 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 3 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 1 records from UWIZM Anoles. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 1 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 222 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 466 records from Pollen analysis of sediment profile TR0 from Truennensee. 1272 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 2451 records from Macrobenthos Chukchi Sea, 1986. 4 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 6 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 140 records from Planktic foraminifera abundance of Hole 37-332. 187 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 4 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 3 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 3 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 798 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 2 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 48 records from Tardigrad collection of the National Museum of Nature and Science. 1862 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 7 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 1714 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 107 records from Faunal assemblage of sediment core TR149-31. 72 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 4747 records from Microbial community in marine sediments. 595 records from Free-living plathelminthes of marine habitats near Wimereux (1990-1991). 28 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 11616 records from Herbier Louis-Marie (QFA) - Collection de lichens. 1012 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 16 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 8 records from Amphibian Specimens of the Yamagata Prefectural Museum. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 129 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 78 records from Planktic foraminifera abundance of Hole 49-409. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 319378 records from Plant. 1 records from A taxonomic review of the genus Asterostegus (Echinodermata: Ophiuroidea), with the description of a new species. 79 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 2 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 49 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 17 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 662 records from Nannofossil abundance of Hole 37-334. 4 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 1 records from New ants (Hymenoptera: Formicidae) from Micronesia. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 774 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 127 records from Total foraminifera counts of multinet M21/2_MSN650. 3001 records from Colecção Entomológica IIA. 1272 records from Flora genérica de las gramíneas del estado de Tlaxcala. 14 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 15760 records from MZFC/Coleccion de Aves. 1 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 261 records from Nannofossil abundance of Hole 84-570. 1049 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 18 records from Leopard and Weddell seal program 1999/2002. 4 records from Natural History Museum Maastricht (NL) - Herbarium. 172 records from Foraminifera abundance of sediment core MD81-LC07. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 35 records from DMNS Egg Collection (Arctos). 426 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 4550 records from MZL Invertebrate Collections. 1138 records from Crustacean specimens of Bihoro Museum. 169 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 2538 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 9 records from New genus and species of cockroaches from the tribe Brachycolini (Blattaria Blaberidae: Blaberinae) and redescription of the Hormetica strumosa. 11603 records from Lepidopterous specimens of Yamagata Prefectural Museum. 411 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1317 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 15581 records from Collection of Coleoptera. 6 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 7 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 170 records from Total foraminifera counts of multinet SO117_MSN1244. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 32 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 125 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 172 records from Orthoptera - SMF. 3577 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 24 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 260 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 13 records from Ensemble des données Rhopalocères. 3 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 137 records from An updated checklist of aquatic plants of Myanmar and Thailand. 2 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 1699 records from BioGIS - Bryophytes - HUJ collections. 2247 records from Ethnobotanical surveys species in Benin (West Africa). 35 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 50 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 2 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 367 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 353 records from Soil invertebrates occurrences in European North-East of Russia. 12 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 365811 records from Queensland Museum provider for OZCAM. 2 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 77 records from Range table from planktonic foraminifers in ODP Hole 182-1133C. 17040 records from Herbarium Universitatis Daugavpiliensis. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1379. 192 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 200 records from Universidad del Valle de Guatemala - Colección de Artrópodos. 158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 103 records from Coccoliths in sediment core GIK23065-3. 22 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 1895 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 385 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 4 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 466 records from Benthic foraminifera counts of sediment core PS1852-2. 2718 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 6642 records from Distribution of foraminifera of sediment core GIK23258-2. 42 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 2 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 14 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 367 records from Nannofossil abundance of Hole 60-458. 16 records from Analyses of the recent components of sediment core PS1277-1. 8630 records from MEXU/Leguminosae. 2 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 42 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 2 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 10 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 5 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 5501 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 425416 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 16 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 1 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 608 records from Range table from benthic foraminifers in ODP Hole 146-889A. 32 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 1 records from Colección de macroalgas de la costa Argentina (IADO-UNS-CONICET). 30109 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 8 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 42 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 402 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 194 records from Planktic foraminifera abundance of Hole 94-610. 138 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 1 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 40 records from The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia. 48211 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 4375 records from SEWBReC Bees, Wasps and Ants (South East Wales). 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 25 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 9 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 7 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 76 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 12 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 1425 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 507 records from COA Bird Collection (Arctos). 112 records from Total foraminifera counts of multinet M33/1_MSN1029. 1857 records from Bryophyte specimens of The Nagoya University Museum. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 267 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 18288 records from University of Guam Insect Collection. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 328324 records from KTP Ring Data. 38 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 26 records from Dinoflagellate abundance of Hole 81-554. 5 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 7831 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 118 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 504 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 23 records from Morphologische Daten von Natrix. 4 records from Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete. 491 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 269 records from UWIZM Molluscs. 1703 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 32 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 692 records from MCP-Aves - Coleção de Aves. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 17 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 6 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 266 records from Nannofossil abundance of Hole 36-329. 43 records from LISU Herbario Angola. 120 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 625 records from Bird specimens of Saitama Museum of Natural History. 72 records from orthopteracollections-nhmj-ioj. 3218 records from CNAC/Coleccion Nacional de Acaros. 1 records from Carnivores of Syria. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 5 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 130 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 5 records from Collections of Bioclass, school #179, Moscow. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 352 records from hauterivian_echinoids_of_the_paris_basin. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 56 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from Muséum d'Avignon. 256 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 36 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 62380 records from natagora-earlybirds. 76 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 5574 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 1 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 20 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 2383 records from Hormigas del Museo de Entomología de la Universidad del Valle. 1 records from Reptiles Specimens of Akita Prefectural Museum. 19 records from UWIZM Snakes. 19 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 113 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 11194 records from University of Minnesota Insect Collection. 155153 records from ARABEL - Arachnologia Belgica. 53998 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 9882 records from Arctic Species Trend Index (ASTI) : Marine. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 256 records from Nannofossil abundance of Hole 85-573. 24510 records from Wolli Creek Preservation Society Bird Survey. 588 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_9-CTD113. 140 records from MLZ Bird Collection (Arctos). 25 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 3 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 1444 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 9 records from Données bibliographiques ASFRA. 33 records from Microzooplankton abundance and biomass at station TT043_27-1. 168 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 11 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 7953 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 1838 records from Gastropod Specimens of the Yamagata Prefectural Museum. 2 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 1033 records from Butterflies_of_Singapore_and_Peninsular_Malaysia_(Nymphalidae). 6524 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 30 records from UWYMV Herpetology Collection (Arctos). 32557 records from FUEL - Herbário da Universidade Estadual de Londrina. 58 records from Atlantic Forestry Centre Insect Reference Collection. 7564 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 58 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 20461 records from Herbarium Senckenbergianum (FR) - Fungi. 1897 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 179 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 98 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 2 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 539 records from Plant specimens of Bihoro Museum. 2136 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 2279 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 98 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 158 records from Planktic foraminifera counts at CTD station PS55/063. 71 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 203 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 612 records from Leicestershire and Rutland Aculeate Records. 11 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 106 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 44 records from Planktic foraminifera abundance of Hole 63-472. 7 records from First report of the old world genus Pelecystola in North America, with description of a new species (Lepidoptera, Tineidae). 1161 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 1310 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 205310 records from First Bird Atlas. 127 records from Institut Mediterrani d'Estudis Avançats (CSIC-UIB): IMEDEA-OTO. 14609 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 19450 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 3 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 5 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 8 records from Reptilia ZMK. 4 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 3645 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 347 records from (Table 3) Relative abundance of selected benthic foraminifera in ODP Hole 104-642C. 141 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 1 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 1 records from Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil. 907 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 7694 records from Inventario de Hymenóptera; parasítica en México. 407 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1 records from New records of Chalcidoidea (Hymenoptera) from the Maltese Islands with an updated checklist. 10 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 3 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 2385 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 3550 records from Ibaraki Nature Museum, Fungi collection. 626 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 8 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 1209 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 26 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 5 records from Révision du genre Danuriella Westwood, 1889 (Mantodea). 230 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 41316 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 11 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 6 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 42 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 1 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 7 records from The types of skippers described by Shu-Iti Murayama (Lepidoptera: Hesperiidae). 5 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 54 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 270 records from Lucanidae. 2456 records from Estación Biológica de Doñana - CSIC, Anfibios. 2361 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 154574 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 9 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 7 records from Hybrizontinae (Hymenoptera, Ichneumonidae), a new subfamily for the fauna of Turkey. 52 records from Birds Specimens of Akita Prefectural Museum. 155 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 1890 records from UAM Fish Collection (Arctos). 2 records from Rideriana amazonica gen. nov. and sp. nov. of Pentatomini (Heteroptera, Pentatomidae). 2 records from New data on the taxonomy and distribution of Philippine Ochodaeidae and description of a new species from Central Visayas (Coleoptera: Scarabaeoidea). 21886 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-71, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 6 records from Bird Specimens of The Cattle Museum. 403 records from Whale catches in the Southern Ocean. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 120 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 78 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 5 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 15052 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 99036 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 201677 records from DATAVES. 5 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 7 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 787 records from Heliconiine Butterfly Collection Records from University of Cambridge. 146 records from The Broward College Insect Collection. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 1 records from Description of Harpactea popovi sp. n. from Bulgaria with further taxonomic notes on related species (Araneae, Dysderidae). 7 records from Planktic foraminifera abundance of Hole 53-418B. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 1635 records from Berea College, Ralph L. Thompson Herbarium. 157 records from Planktic foraminifera counts at CTD station PS55/078-1. 11 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 424 records from Distribution of nanoplankton at trap WR2. 14 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 6421 records from Fish specimens of Toyama Science Museum. 61 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 132 records from Range table from ostracoda in ODP Hole 143-866B. 1 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 5 records from Anderemaeus (Acari, Oribatida) - overview, three new species from South America and reassessment of Anderemaeidae supported by ontogeny. 913 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 6 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 84 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 210 records from Colección Limnológica Universidad de Antioquia. 20 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 33555 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 45099 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 167 records from Isle of Wight non-native invasive species. 2 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 5181 records from Données naturalistes de LUPOLI Roland. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 1 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 1144 records from Weber State University Herbarium. 1 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 903 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 14528 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 230 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 124 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 767 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 5376 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 69 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 91 records from Diatom abundance of Hole 95-613. 582 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 23 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 10132 records from Lepidoptera specimen database of Japan. 6 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 1406 records from Leicestershire and Rutland Reptile Records to 2011. 196414 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 2144 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 77 records from Smear slide analysis on sediment core GeoB4214-1. 23 records from Abundance of benthos infauna at station GIK23042-2. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 104 records from Collection Vermes - ZMB. 618 records from Culture Collection of Algae. 1494 records from SIM-Fungal records compiled by Joan Montón. 374 records from Planktic foraminifera abundance of Hole 68-503B. 253529 records from Western Australian Museum provider for OZCAM. 1152 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 2 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 3977 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 690 records from Benthic foraminifera counts of sediment core GIK23352-3. 417 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 1054081 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 552 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 52 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 173 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 1 records from Glossostyles perspicua gen. et sp. nov. and other fungivorous Cecidomyiidae (Diptera) new to the Czech and Slovak Republics. 3 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 13 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1502 records from M. Gollop Collection. 622 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 23665 records from Naturalis Biodiversity Center (NL) - Diptera. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 22 records from Coccolith counts of multinet SO119_MSN1272. 272 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 480 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 4 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 735 records from Nannofossil abundance of Hole 75-532. 2275 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 15 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 24 records from Benthic macrofauna abundance of sediment core 13200-008. 1830 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 69 records from Foraminifera species abundances from tow TT007_7-MOC13. 31 records from Nannofossil abundance of Hole 94-611E. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 127 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 4529 records from ERBG AVH data. 10 records from CABI Africa Invasive and Alien Species data. 451 records from River Biologists' Database (EPA). 11 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 8682 records from Banded Iron Formation and Greenstone survey data. 3288 records from UCM Mammal Collection (Arctos). 28 records from Microzooplankton abundance and biomass at station TT045_19-3. 2 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 5 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 71043 records from Tiroler Landesmuseum Ferdinandeum. 37 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 8 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 60941 records from Natural History Museum, Vienna - Herbarium W. 35 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 1780 records from Odonata records from RSPB Reserves 1970-2009. 4 records from Données supplémentaires Atlas des Mammifères marins. 13379 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 489 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 91 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 160 records from Abundance of radiolaria at station UT99-23-2. 488484 records from NBIS Records to December 2016. 27 records from Planktic foraminifera abundance of Hole 51-417B. 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 1347 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 499 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 39 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 208 records from South American Antarctic Marine Biodiversity Literature. 114810 records from Arizona State University Vascular Plant Herbarium. 747 records from Stoneworts in Wales. 4 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 2 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 1323 records from Fungi Collection. 1001 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 51 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 185 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 15 records from Meiofauna abundance in sediment core 54301-010. 2 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 3561 records from Biogeography of near-shore reef fishes in northern New Zealand. 62288 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 100 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 1 records from The InBIO Barcoding Initiative Database: A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann, 1870 (Lepidoptera, Depressariidae). 20643 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 4318 records from NE Scotland other invertebrate records 1800-2010. 179 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 408 records from Range table from planktonic foraminifers in ODP Hole 182-1129C. 40323 records from NE AVH data. 147 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla (Plantas). 46 records from Total foraminifera counts of multinet M21/5_MSN742. 6198 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 3 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 9 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 3582 records from Données Entomologiques A. HORELLOU 1988-2018. 558 records from Foraminifera abundance of Hole 74-526A. 1105 records from Enquête Lucane. 267 records from Dinoflagellate abundance of Hole 81-555. 1663 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 4 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 266 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 54930 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 607 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 5 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 63 records from Herbier National de Guinée (HNG). 31 records from Benthic foraminifera abundance of Hole 42-379A. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 1 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 390 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 15 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 1462 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 1851 records from Global compendium of Aedes albopictus occurrence. 327 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 9 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 49 records from Coccoliths in sediment core PS1535-8. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 203789 records from Flora Atlas N.T.. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 3969 records from Fishes in the Argentine Sea from 1967 to the present time. 23 records from Benthic foraminifera abundance of Hole 93-603. 2 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 7457 records from WOLL AVH data. 3904 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 85 records from Ostracoda abundance of Hole 48-403. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 226 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 21 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 1589 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 172 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 576 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 4361 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 21 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 899 records from Stable isotopes and content of foraminifera at Hole 130-805C. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1360 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 2 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 1 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 429 records from Foraminifera abundance of Hole 64-481. 19 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 1782 records from Butterflies of Ireland. 3 records from Review of the Australian Signal Flies of the Genus Microepicausta (Diptera: Platystomatidae). 547 records from Rare plants database extract from Scottish Natural Heritage. 14 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 1921 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 697 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 32444 records from MDFRC macroinvertebrate survey. 36 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 8125 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 96 records from Plasm bearing foraminifera counts of multinet M21/1_MSN620. 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 126 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 167 records from Plecoptera. 123 records from Range table from benthic foraminifers in ODP Hole 146-889B. 1 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 10 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 5 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 1 records from Données naturalistes d'Arnaud LE NEVÉ. 4 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 1 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 23798 records from Swan Coastal Plain Survey. 599 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 9 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 65 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 10 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 3 records from NZCS Brownsberg Nature Park Monitoring. 23 records from Analyses of the recent components of sediment core PS1219-1. 154 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 42 records from Review of the genus Paramesius Westwood, 1832 (Hymenoptera: Diapriidae, Spilomicrini) from Russia, with description of four new species. 38904 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 106 records from HBRG Invasive Non-native Plants Dataset. 11199 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 774 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 478 records from Neogene palynomorpha from site 81-552. 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 73 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 851 records from Pollen profile V and Ausfluss at Krumbach, Germany. 170 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 59302 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 681 records from RECORD Orthoptera Data. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 2 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 1 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 6987 records from Birds Specimens. 24776 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 10 records from Oberservation of birds at station PS14/143 along 49° West. 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 1 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 36 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 5266 records from Upper Silesian Museum, Bird Observations. 1525 records from ISM Ichthyology Collection. 68 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 3993 records from DMNS Mammal Collection (Arctos). 70 records from Entomological collection of the National Museum. 57919 records from Fichier communal des ongulés. 213 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 53 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 1 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 1 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 6 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 49056 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 2 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 31 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 1 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2069 records from Helmintos parásitos de peces del sureste de México. 604 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 281 records from Range table from benthic foraminifers in ODP Hole 159-959A. 469 records from Radiolaria assemblage in sediment core GIK23259-2. 5 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 2 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 19 records from Données naturalistes de Charlotte PICARD. 5 records from Ostracoda abundance of Hole 44-390. 5 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 58 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 4854 records from University of California Santa Barbara Invertebrate Zoology Collection. 310 records from Données naturalistes de Hervé BOUYON. 522 records from Données de la collection Rousset -1947-2013. 1 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 25 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 13773 records from Entomology Collection at the Natural History Museum of Utah. 673 records from Planktic foraminifera abundance of Hole 45-395. 111 records from Total foraminifera counts of multinet M21/2_MSN629. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 154 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 911 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 169854 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 40380 records from ALCB - Herbário Alexandre Leal Costa. 152 records from Total foraminifera counts of multinet POS247/2_MSN1372. 21 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 1 records from Dinoflagellate abundance of Hole 85-572C. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 8611 records from Fish specimens of Kagoshima University Museum. 38 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 6522 records from UTEP Invertebrates (Arctos). 452 records from Diptera Collection of Museum and Institute of Zoology PAS. 74 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 654 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 1 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 99 records from Total foraminifera counts from M35/1_MSN1061. 342 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 23643 records from CNIN/Abejas de México/Apoidea. 710 records from RNF - Données du Parc Naturel Régional du Vercors. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 1968 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 1422 records from Flora útil del Municipio de la Huerta, Jalisco. 1116 records from Insectes Hyménoptères Scollidés de France. 1075 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 108 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 878 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 1159 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 625 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1212 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 159 records from Total foraminifera counts of multinet M36/6_MSN1196. 347 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 503 records from IOW Natural History & Archaeological Society Marine Records. 124 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 200 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 7 records from Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species. 2 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 3 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 152 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 84 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 3876 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 210 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 23 records from Benthic macrofauna abundance of sediment core 13077-093. 1 records from Invasive Non-Native Species, Outer Hebrides. 221256 records from Phase 2 Lowland Grassland Survey of Wales. 19657 records from Naturalis Biodiversity Center (NL) - Crustacea. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 3 records from Données de NICOLAS Vincent (SAPROX). 1 records from Brown algae specimens of Komatsu City Museum. 2562 records from Danish Ants (Formicidae). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 24 records from Benthic macrofauna abundance of sediment core 13201-002. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 225 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1415 records from MSUM Ichthyology and Herpetology Collections. 1 records from Planktic foraminifera abundance of Hole 54-420A. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 5 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 12530 records from DIBA-Parc del Montnegre i el Corredor. 4282 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 179 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 225 records from Planktic foraminifera abundance of Hole 40-362A. 33483 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 16 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 2 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 57 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 11260 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 18 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle RNC:102. 1 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 6 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 3 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 1390 records from Herbario de la Sociedad Micológica Barakaldo Mikologia Elkartea. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 4 records from Catalogue of the Syrphidae of Egypt (Diptera). 61 records from Range table from planktonic foraminifers in ODP Hole 167-1010E. 1 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 27 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 3564 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 560 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 9579 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 2410 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 33698 records from MCP - Coleção de Abelhas. 67 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 49 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 3 records from New state records of lady beetles (Coleoptera: Coccinellidae: Coccinellinae) from Missouri and Mississippi, USA. 4 records from SCFS - Sagehen Herbarium. 134 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 10 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 1 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 16403 records from Données naturalistes de Pascal Dupont. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 327 records from K-State Museum of Entomological and Prairie Arthropod Research. 239 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 18890 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 67 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 173 records from Bird specimens of Bihoro Museum. 1 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 876 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 16 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 329 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 92 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 3 records from A new species of Bicoxidens Attems, 1928 (Diplopoda, Spirostreptida, Spirostreptidae) from northern Zimbabwe. 564 records from Zootaxa. 402 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 1 records from A review of South Korean Alloplasta Förster (Hymenoptera: Ichneumonidae: Banchinae) with description of a new species. 6311 records from NBMB Herps. 303 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 386 records from Foraminifera distribution of sediment core KS310. 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 247 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 170 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 22 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 3187 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 11877 records from Données naturalistes de Monsieur François FOURNIER. 2 records from NHMO DNA Bank Other groups collection. 635 records from Revues diverses et littérature grise.. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 12 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 114 records from (Table 4) Thecosomata in ODP Hole 134-831A. 23463 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 22 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 1784 records from Distribution of planktic foraminifera of sediment core M33/1_SL_NAST. 5 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 5330 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 1 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 880 records from Distribution of major planktic foraminifer at Site 177-1093. 562 records from Expedición Providencia I - INVEMAR. 56 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 18293 records from University of Michigan Museum of Zoology, Division of Birds. 2 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 95448 records from Hatikka Observation Database. 105 records from UWYMV Bird Collection (Arctos). 74 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 1921 records from Foraminifera abundance of Hole 61-462. 640 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 93680 records from inatura - Erlebnis Naturschau Dornbirn. 2 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 409 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 27 records from Collection Graptolithina fossil SMF. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 273 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 55708 records from PlutoF platform observations. 12861 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 9 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 45 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 26 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 8 records from The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms. 43 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 15 records from Benthic macrofauna abundance of sediment core 13078-015. 1082 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 10 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1297 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 688879 records from Fungal Records Database of Britain and Ireland. 2408 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 30268 records from Insect specimen database of Atsugi City Museum. 8523 records from Nematoda of Costa Rica (INBio). 3 records from Revision of the genus Psorus Bergroth, 1914 (Hemiptera: Pentatomidae: Discocephalinae). 3 records from Microplankton counts and carbon biomass at station TT007_9-CTD108. 1051 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 131 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 14 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 551 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 6 records from Foraminifera abundance of Hole 58-442. 626 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 87 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 29 records from Colección Entomológica CDMB. 1042 records from NZCS Invertebrates New Collection After 1987. 182 records from (Fig. 10) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 41-367 in the North Atlantic. 10371 records from Lepidoptera (Specimens NRM). 2 records from Coleção de Coleoptera da Universidade de Brasília. 3316 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 9 records from Colección nacional de palmas de Colombia - JBQ. 939 records from ROC RSPB Farmland Species Survey Dataset. 972 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 7 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 182049 records from Florida Keys Reef Visual Census 1999. 4419 records from Marie-Victorin Herbarium (MT) - Bryophytes. 18 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 108 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 6220 records from Collection of saproxylic and xylobiont Beetles. 142680 records from National Benthic Inventory. 140 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 14 records from Phenological Center - Fishes (Murmansk). 181 records from Dinoflagellate cysts from sediment core PS1295-4. 17 records from Phenological Center - Mushrooms (Karelia). 6884 records from Tachinid Recording Scheme - GB and Ireland records. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 1148 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 8 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 192 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 3 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 8332 records from Scotland Otter Survey Database. 1 records from A review of bat research in Thailand with eight new species records for the country. 275 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 458 records from Utah State University, Intermountain Herbarium. 2 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 146680 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 659 records from Canadian Museum of Nature Palynology Collection. 1 records from The Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) of Nepal. 1245 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 143 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 261 records from Planktic foraminifera abundance of Hole 63-469. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 1 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 1 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 36 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 136 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 108 records from Range table from benthic foraminifers in ODP Hole 172-1060B. 43648 records from CAS Entomology (ENT). 32 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 169 records from Range table from planktonic foraminifers in ODP Hole 170-1041A. 3154 records from Carnet B Lorraine. 8502 records from Naturalis Biodiversity Center (NL) - Pisces. 6 records from Cybaeus (Araneae: Cybaeidae): the adenes species group of the Californian clade. 21 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 480 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 473 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 705 records from (Table 1) Pleistocene planktonic foraminiferal assemblages at ODP Site 128-798. 4 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 589 records from Radiolaria assemblage in sediment core GIK23414-6. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 136 records from Myxomycetes collection of the University of Eastern Finland. 24 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 19756 records from Seasearch Marine Surveys in England. 129 records from Plasm bearing foraminifera counts of multinet M21/2_MSN657. 38 records from Planktic foraminifera abundance of Hole 84-566C. 1 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 51 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 182 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from planktic foraminifera. 165 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 4 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 2290 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 3466 records from Collection Trichoptera - SMF. 5430 records from Insectes Hétéroptères Mirides de France. 4966 records from Range table from nannofossils in ODP Hole 164-994C. 1552 records from Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 701 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 32 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 1200 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 749 records from Pollen analysis of sediment core GeoB6518-1. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 3776 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 28528 records from Arizona State University Hasbrouck Insect Collection. 698 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 63228 records from CCAMLR historic KRILL. 1 records from Collection Strepsiptera SMF. 94 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 1735 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 1 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 12 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 2 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 1 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 2799 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 8 records from Range table from benthic foraminifers in ODP Hole 139-856C. 359 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 3404 records from Lista florística de la Costa Grande del estado de Guerrero. 41 records from Range table from planktonic foraminifers in ODP Hole 169-1036B. 3 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 14 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 7 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 2400 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 68153 records from NINA Vanndata fisk. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 144 records from Total foraminifera counts of multinet POS247/2_MSN1386. 2 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 1 records from New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean. 602 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 10079 records from CSIRO, fish surveys by the Soela, 1980s. 1 records from A new species and additional records of brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China and Taiwan. 16 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 1475 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 1 records from Notes on the grasshopper genera Longgenacris You & Li, 1983 and Fruhstorferiola Willemse, 1922 (Orthoptera: Acrididae: Melanoplinae) with proposal of a new synonym. 439 records from Nannofossil abundance of Hole 78-543. 1399 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 299 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 18928 records from British Antarctic Survey Argos satellite tracking data. 8512 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 260 records from Planktic foraminifera assemblage in sediment core GIK17045-3. 30 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 776 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 24 records from A review of Synegiodes Swinhoe, 1892 (Lepidoptera: Geometridae), with description of two new species. 114 records from Total foraminifera counts of multinet M26/1_MSN844. 22 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 35 records from Total foraminifera counts of multinet FCA97C_MSN1339. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 26 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 5251 records from University Of Pretoria: Lacewing Database Project (1911-2015). 2540 records from USAC Mammals Collection. 435 records from Nannofossil abundance of Hole 66-490. 165 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 205 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 66 records from Données du naturaliste Doux Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 3415 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 1 records from On some species of the genus Acrolocha Thomson, 1858 of the Western Palaearctic Region (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 1 records from Données du naturaliste Christian Desmier. 2594 records from Stone-curlew Annual Surveys. 6 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 1545 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 145 records from Fossil Specimens of Komatsu City Museum. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 749 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 1197 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 78 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 296 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 870 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 1 records from Taxonomic review of the genus Wasmannia.. 191 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 1516 records from Données naturalistes de Bernard Lalanne-Cassou. 383 records from Données naturalistes de Franck NOEL. 27 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 2 records from PSUZC-Reptile Collection. 1251 records from Nannofossil abundance of Hole 82-558A. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 389 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 31 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1 records from A new species of Oncopeltus Stål, 1868 (Heteroptera: Lygaeidae) in the nominate subgenus from Ecuador. 1497 records from BioGIS - Mammals - SPNI. 635 records from Carnarvon Basin wetland survey. 20 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 9543 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 13 records from Diatom abundance of Hole 60-460. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 234 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 73262 records from SEWBReC Birds (South East Wales). 154 records from Total foraminifera counts from multinet SO119_MSN1285. 2945 records from Collection Echinodermata SMF. 8 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 22 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 782 records from Planktic foraminifera abundance of Hole 42-372. 2716 records from MEXU/Flora de Oaxaca. 3405 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 4 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 1 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 2574 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 290 records from Nannofossil abundance of Hole 66-488. 72 records from Heavy minerals of sediment core PL94-64. 74309 records from Amphibiens et Reptiles de France (Enquête 2). 67 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 3 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 66 records from Données naturalistes d'Alain BERLY. 7523 records from Herps Specimens. 23819 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 14 records from Données opportunistes. 752 records from Red-throated diver national surveys in Scotland - raw data. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 368 records from Ring ouzel national sample survey in the UK in 1999. 149 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 4 records from Inventaire et regroupement de données Natura 2000. 1007 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 30239 records from Données de la flore d’Alsace (SBA). 3 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 2 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 3 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3193 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 150 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 375 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 58 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 46 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 3 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 2842 records from Distribution of major planktic foraminifer at Site 177-1090. 128 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 4599 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 157 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 66 records from Données naturalistes de Quentin ROME. 243 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 39 records from SEWBReC Springtails and allies (South East Wales). 2353 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 2076 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 21 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 26 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 69059 records from The Himalayan Uplands Plant database (HUP Version 1). 1 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 2380 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 9096 records from National Museum of Natural Science. 1565 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 9 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1 records from First record of the genus Dictyopharina Melichar, 1903 (Hemiptera: Fulgoroidea: Dictyopharidae) from China, with descriptions of two new species. 67 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 17 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1575 records from Hermatypic Corals of Western Australia. 20 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 4068 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 18 records from Collections ichtyologiques et herpétologiques (BOUM). 970 records from MCP-Mamiferos - Coleção de Mamíferos. 19 records from Benthic macrofauna abundance of sediment core 12930-073. 4780 records from Données naturalistes de Bruno OGER. 11033 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 582 records from Stable isotope data and sedimentology of core SO42-74KL. 40 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 81 records from Meniscus Midges (Dixidae) of Ireland. 2 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 11166 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 330 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 2353 records from NE Scotland fish records 1800-2010. 63206 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 3145 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 671 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 50 records from Zambian Bat Collections Worldwide. 4 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 4 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 256 records from bmhs_weatherheadshell_collection. 97 records from Foraminifera species abundances from tow TT011_7-MOC66. 14176 records from Vascular plants of south-central China. 315 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 8 records from Données des collections d'algues du MNHN. 3190 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 8209 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 209 records from Coléoptères Silphidés du département du Loiret. 148 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 258251 records from NOAA AFSC North Pacific Groundfish Observer. 5840 records from Formidabel; Belgian Ants Database. 2356 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 4 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 18 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 34 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 145 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 68711 records from CAS Invertebrate Zoology (IZ). 313 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 3 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 3 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 29 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 123 records from Total foraminifera counts of multinet M21/4_MSN694. 5978 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 697 records from Insects, Outer Hebrides. 35 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 710 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 639 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 93 records from Journal of Hymenoptera Research. 155 records from Total foraminifera counts of multinet M21/2_MSN643. 130 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 19 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 74 records from Capercaillie national surveys. 1 records from Description of two new Homoeocera Felder from Guatemala and Mexico (Lepidoptera, Arctiidae, Arctiinae, Euchromiini). 44233 records from La familia Asteraceae en México. Fase VI. 356 records from Morphologische Daten von Puffinus creatopus. 19616 records from WTSWW Data: All Taxa (West Wales). 131 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 825 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 100143 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 178 records from Mycological collection of the National Museum. 21 records from Salticidae (Arachnida: Araneae) of New Caledonia: Genus Corambis Simon, 1901. 202 records from Range table from benthic foraminifers in ODP Hole 174-1073A. 2 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 168937 records from South Australian Museum Australia provider for OZCAM. 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 35 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 5 records from Coccolith counts of multinet M32/5_MSN981. 78 records from Herbarium BSG Hepaticopsida. 5 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 17 records from Brock University Herbarium (BU). 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 9 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 9716 records from SIO Benthic Invertebrate Collection. 2857 records from Whicher Scarp Flora Survey. 9596 records from DASSH Data Archive Centre volunteer survey data. 134 records from Range table from planktonic foraminifers in ODP Hole 177-1088C. 2 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 9 records from Plasm bearing foraminifera counts from multinet M31/2_MSN890. 3 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 41 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 11 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 7 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 67 records from Modernisation des ZNIEFF du PnrL. 16 records from Dinoflagellate cysts of surface sediments. 7 records from Collection Malakologie - SMNG. 20 records from UWIZM Cnidarians. 15 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 354 records from Antarctic and Subantarctic Asteroid zoogeography. 1 records from New species and records of Omaliini from East Asia (Coleoptera: Staphylinidae: Omaliinae). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 1464 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 191 records from Nannofossil abundance of Hole 67-499. 48 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 48196 records from Tasmanian Museum and Art Gallery provider for OZCAM. 185 records from TTRS Mammals. 4 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 744 records from Ostracoda in sediment core PS51/159-10. 2 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 7 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 3 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 212 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 2 records from Benthic foraminifera abundance of Hole 42-376. 90 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 3 records from Review Of The Species Of Conomorium Masi (Hymenoptera: Pteromalidae). 372 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 677 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 63 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 1836 records from Phytoplankton abundance in surface water in October 1996, Ilo, Peru. 2160 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 230 records from UTEP Fish (Arctos). 26 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 42 records from The caddisfly genus Protoptila in Costa Rica (Trichoptera: Glossosomatidae). 14 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 22294 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 138 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 72 records from Modelación de la distribución potencial del género Bursera (Burseraceae) en México. 27307 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 207 records from University of Sindh Jamshoro Herbarium. 1 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 2365 records from (Table S2a) Nannofossil species richness in the Bass River section. 8 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 17 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 128 records from Faunal assemblage of sediment core TR149-32. 1 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 75 records from Registros Primates Neotropicales Convocatoria APC. 2 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 4031 records from Benthic foraminifera distribution of sediment core GIK17957-2. 2 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 12963 records from Mollusques dulcicoles de France - Jacques MOUTHON. 2156 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 60 records from BID-Malawi-Geometridae-Biodiversity-Data. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 360 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 32 records from Foraminifera species abundances from tow TT007_15-MOC23. 81 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 520 records from Collection Aves (bird skins) SMF. 6 records from Revision of Arcastes Baly, 1865 from the Oriental Region (Coleoptera, Chrysomelidae, Galerucinae). 11 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 9 records from Taxonomic revision of the genus Probolomyrmex Mayr, 1901 (Hymenoptera: Formicidae: Proceratiinae) for the Neotropical Region. 5037 records from La familia Asclepiadaceae en México. 4053 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 8 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 311 records from Benthic foraminifera abundance of Hole 41-366A. 1 records from Otter survey of Ireland 2004 & 2005. 457 records from JOI - Herbário Joinvillea. 19 records from A revision of the African wolf spider genus Amblyothele Simon. 232 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 2 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 5 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 52 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 6 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 45872 records from The national database for marine data (MADS). 204 records from Foraminifera abundance of Hole 57-440A. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2332 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 55 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 102 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 3614 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 70 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 3444 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 12 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 190 records from Leicestershire and Rutland Mature trees Inventory 2011. 362 records from Pollen data of trap CB4. 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 1 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 19 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 24894 records from Plan de vertebrados de la Patagonia. 4 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 4515 records from Distribution of planktic foraminifera of sediment core M35003-4. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 148 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1694 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 2 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 40 records from LPO_PACA_2017_12_18. 9 records from Nannofossil abundance of Hole 39-353A. 216 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 10 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 74 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 3340 records from Census of species recorded during phytosociological surveys in Benin. 1239 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 1596 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 3570 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 1 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 18 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 7152 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 73 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 7570 records from Collection Pisces SMF. 195 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 3951 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 2514 records from MEXU/Tipos de plantas vasculares. 15 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 444 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4399 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 84 records from Total foraminifera counts from M35/1_MSN1051. 23 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 49 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 462 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 5 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 201 records from Total foraminifera counts of multinet M21/1_MSN606. 3006 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 23489 records from Estonian Nature Observations Database. 6 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 10 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 1 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 33750 records from Botanical Museum, Copenhagen, Mycology Herbarium. 5868 records from NCSM Mammals Collection. 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 41 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 1 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 855 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 25065 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 25436 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 4 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 30 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 2 records from Planktic foraminifera counts of multinet PS2616-5. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 323 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 13249 records from Fife Nature Records Centre combined dataset. 54 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 1 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 1 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 20 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 34 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 5744 records from Odonata de Veracruz. 108 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 224 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 205 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 324 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 203 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 1 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 2 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 9 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 210 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 14 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 5809 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 535 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 491 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 127 records from Total foraminifera counts of multinet M21/2_MSN650. 200 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 178 records from (Table 9) Relative abundance of benthic foraminifera in ODP Hole 112-685A. 3 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 6 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 2 records from Vermont Orthoptera Records from Historic Dot Maps. 159 records from Nannofossil abundance of Hole 67-499B. 46 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 181 records from Total foraminifera counts from multinet M31/3_MSN915. 393824 records from NatureServe Network Species Occurrence Data. 1529 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 2204 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 946 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 182 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 1709 records from The Gibson spider collection. 29 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 34286 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 2 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 1 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 4275 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 1256 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 18 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 19 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 61 records from données araneologiques de LEENKNEGT Virginie. 11 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 1 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 9 records from Colección de helechos de la FML. 66164 records from Florida Keys Reef Visual Census 1996. 107 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 74 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 13377 records from Données de l'Observatoire de la Faune de Bourgogne. 1184 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 864 records from Neogene palynomorpha from site 93-603, part 2. 2 records from Revision of the types of species of Alloxysta described by Cameron and Fergusson (Hymenoptera: Figitidae: Charipinae) and deposited in the Natural History Museum (London), including a key to the fauna of Great Britain. 1074 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 6 records from Review of the leafhopper genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species. 55379 records from Wild bees of Belgium. 3 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 546 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 4 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 191 records from Phenological Center - Birds (Murmansk). 9 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 2 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera, Platygastroidea, Platygastridae) from South Africa. 212 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 2064 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 16 records from Aspilanta new genus (Heliozelidae) specimen data. 22 records from Echinoderms from the Seaflower Biosphere Reserve. 300 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 684 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 30 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 868 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 9 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 230 records from Nannofossil abundance of Hole 49-408. 874 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 109720 records from Allan Herbarium (CHR). 23 records from Analyses of the recent components of sediment core PS1011-1. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 50894 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 565 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Plantas Tapachula). 3438 records from Royal British Columbia Museum Entomology Collection. 3 records from Taxonomic revision of West African cone snails (Gastropoda: Conidae) based upon mitogenomic studies: implications for conservation. 44 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 13803 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 4 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 106 records from Dinoflagellate abundance of Hole 81-552. 111 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 315 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 2 records from Four new species and new records of the Neotropical genus Alloraphes Franz (Coleoptera: Staphylinidae: Scydmaeninae). 2 records from MVZ Herp Observations (Arctos). 324 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 17 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 126 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 172 records from checklist-of-birds-of-zomba-mountain. 62111 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 17 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 2 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 4644 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 1762 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1139118 records from Flore Franco-Belge. 32771 records from EAC - Herbário Prisco Bezerra. 212 records from East Ayrshire Species Database. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 2700 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 9 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 20 records from Leif Richardson Vermont Bee Specimens. 12 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 260 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 902 records from Collection Crustacea - ZMB. 174 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 571 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 11 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 94 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 4 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 128 records from Wichita State University Collection. 26989 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 111 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 1 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 173 records from pbzt_insect_biodiversity. 245 records from NZCS Upper Tapanahony Expedition 1991. 133 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 6 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 1 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 27689 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 1 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 5 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 1 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 40 records from Coleção de Nematoda do Museu Nacional - UFRJ. 398 records from Inventory of plant species through Benin (West Africa). 5 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 553 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 3 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 2 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1123 records from Planktic foraminifera abundance of Hole 72-516F. 1803 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1 records from Benthic foraminifera abundance of Hole 96-624. 3216 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 517 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 11 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 2102 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 2729 records from Fungi specimens of Saitama Museum of Natural History. 786 records from Mollusca Collection of Saitama Museum of Natural History. 841 records from Planktic foraminifera abundance of Hole 72-518. 42 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 630 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 16 records from Nemertini - SMF. 665 records from Bosque Mesófilo de Montaña de México. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 765 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 21501 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 12 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1 records from Collection ornithologique A. Maës. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 1632 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 3791 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 29 records from Mammal specimens of Komatsu City Museum. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 9158 records from National Stag Beetle Surveys (Great Stag Hunts). 1989 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 294662 records from Eremaea. 14 records from Benthic foraminifera abundance of Hole 96-620. 105 records from Nanoplankton abundance at station GeoB2006-4. 16 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 4704 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 122866 records from Herbarium of Taiwan Forestry Research Institute. 1 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 14 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 5644 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 221 records from Données odonates. 159 records from Malawi-Histeridae-Biodiversity-Data. 23828 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 503 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 11 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 52 records from Benthic foraminifera and algae abundance of Hole 35-325. 25 records from Microzooplankton abundance and biomass at station TT043_4-1. 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 3082 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3708 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 15535 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 30 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 7 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 276 records from Carabidae of the European North-East of Russia. 3560 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 2 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4046 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 6 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1564 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 10 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 6 records from Abundance of benthos infauna at station GIK23065-1. 14277 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 8 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 1 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 1617109 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 2 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 157 records from Bishop's University Insect Collection (BUIC). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 48049 records from BioFokus. 2 records from Anymals+plants - Citizen Science Data. 995 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 18671 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 886 records from CNAN/Scorpiones. 60 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 96 records from Total foraminifera counts of multinet M26/1_MSN845. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 2 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 3 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 94 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 1 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 3 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 177 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 790 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 113 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 8 records from A new leafhopper genus Discolopeus and nine new species (Hemiptera, Cicadellidae, Deltocephalinae) associated with shrubs, trees and poisonous plants in South Africa. 27 records from Сypripedium guttatum Sw. in the Komi republic. 77 records from Nannofossil abundance of Hole 73-521A. 913 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 954 records from BioGIS - Vascular plants - Israeli Gene Bank. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 4 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 3 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 6086 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 7493 records from NSW South Coast & ACT plants. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 118 records from Radiolaria assemblage in sediment core GIK23400-3. 877 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 148 records from Abundance of birds in the Lena Delta Region. 95 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 1835 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 124 records from Kirkliston Range stream monitoring. 2102 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 60 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 381 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 433 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 12 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 2420 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 4 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 10122 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 642 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 1 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 1936 records from Colección Ornitológica de la Universidad del Valle. 356 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 5649 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 9 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 45 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 88 records from Total foraminifera counts from M35/1_MSN1065. 1 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 25 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 1466 records from Marine Turtles. 4095 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1672 records from Composition of the coccolith flora in sediment core GeoB1710-3. 167 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 37 records from Collection Ephemeroptera - SMF. 5 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 33 records from Microzooplankton abundance and biomass at station TT045_15-2. 3402 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 11208 records from Denver Museum of Nature & Science - Entomology. 1 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 19226 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 146 records from Database for alien invasive plants occurrences in Germany. 11 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 11 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 6196 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 172 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 84 records from Benthic foraminifera abundance of Hole 84-566C. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 7221 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 15 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 23295 records from National Biodiversity Data Bank. Observation records, 1900-2014. 146 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 6 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 3314 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 3 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 114 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 106 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 32 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 343 records from Nannofossil abundance of Hole 37-333. 3 records from Amoeboid protists isolated from ancient Siberian permafrost. 2463 records from Inventaire des Mollusques Sphaeriidae de France. 2838 records from données aranéologiques de CORNIC Jean-François. 31 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 78 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 1647 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1498 records from Diatom assamblage in samples from sediment trap OG5. 3 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 5 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 2076 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 1269 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 85616 records from MICROBIS database. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 58 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 4 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 4701 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 88860 records from Swiss National Orthoptera Databank. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 2861 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 17635 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 1288 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 13 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 16 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 588 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 129 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 33 records from Fish Fauna of Berlin. 9 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 1752 records from Phytoplankton abundance in surface water during cruise CD61. 709 records from Kherson State University herbarium (KHER), Department of Botany. 29 records from Total foraminifera counts of trap L3_92_45. 159 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 2971 records from Nijmegen Natural History Museum (NL) - Herbarium. 907263 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 4426 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 107 records from Total foraminifera counts of trap L2_92_A42. 30 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 8 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 29083 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 52 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 183 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 2058 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 7 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 56 records from Annales de la Société entomologique de France [1832- ]. 44 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 64648 records from Hymenoptera specimen database of Kyushu University. 343 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 1 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 161742 records from Finnish Floristic Database (Literature Sources). 31 records from The Myriapoda Collection of the National Museum of Nature and Science. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 1 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 2492 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 14016 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 1 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 32552 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 8 records from Conservatoire Botanique Pierre Fabre. 175 records from Nannofossil abundance of Hole 41-366A. 1820 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 2 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 152 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 513 records from Planktic foraminifera abundance of Hole 84-567A. 7 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 1950 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 155 records from Nannofossil abundance of Hole 39-359. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 4 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 11 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 128 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 153 records from Nannofossil abundance of Hole 49-412. 26 records from Abundance of benthos infauna at station PS1240-1. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 29 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 688 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 425 records from données arachnologiques de CARR David. 5 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 196 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 17 records from Musée Vert ornithology collection. 39 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 3 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 1350 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 357 records from Feeding rhythms of the common goby Pomatoschistus microps at the brackish tidal marsh 'Het verdronken land van Saeftinge' in 1994. 17909 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 8400 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 1128 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 9 records from Planktic foraminifera abundance of Hole 94-611B. 1736 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 1 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 2584 records from Range table from benthic foraminifers in ODP Hole 154-929A. 2 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 10 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 46664 records from Derek Lott Coleoptera Dataset. 13578 records from JCT AVH data. 20362 records from University of Tennessee Bryophyte Herbarium. 3241 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 710 records from Likona Invertebrates. 66 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 128888 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 412 records from Amphibiens de Guyane. 182 records from Planktic foraminifera abundance of Hole 62-465. 7 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 1253 records from Nannofossil abundance of Hole 75-530A. 2895 records from DBRC Hemiptera species records 1969 to 2015. 1 records from Collection Myriapoda - SNSD. 57607 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1380 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 1954 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 39 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 2635 records from Dorset SW Pilot species dataset. 42 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 20 records from Benthic macrofauna abundance of sediment core 13077-087. 348 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 2112 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 3264 records from Cumbria Non Native Invasive Species. 596 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 371 records from Benthic foraminifera and algae abundance of Hole 81-554A. 1128 records from Diatom assamblage in samples from sediment trap OG4. 383 records from DAR AVH data. 93869 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 376 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 217 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 173 records from DBL_Life. 257 records from Océanopolis mammifères marins en Bretagne 1993-2015. 10807 records from BLS Rare and Threatened Lichen Records: England. 5722 records from NCSM Non-molluscan Invertebrates Collection. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 310 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 98872 records from The AAU Herbarium Database. 4 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 4 records from A review of the ant genus Metapone Forel from Madagascar.. 1 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 1376 records from The Vascular Plants Collection of the University of Goettingen. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 2 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 1485 records from Flora vascular acuática de la cuenca del Río Tamesí. 18 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 379 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 22 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 1895 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 2 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 93 records from Andes to Amazon Biodiversity Program. 3715 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 750 records from Données naturalistes de Stéphane ORIO. 32 records from Inventario herpetofaunístico del noroeste de Hidalgo. 406 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 6 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 54 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 164 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 13 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 2 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 1 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 28 records from Jardín Botánico Atlántico, Gijón: JBAG. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 1 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 567 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 9 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1336 records from Colecção Entomológica do Museu de História Natural de Maputo. 1 records from A new species of Umanella Gauld (Hymenoptera, Ichneumonidae) from Ecuador. 11 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 241 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 42 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 284 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 429 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 1121 records from Collection Polychaeta - ZSRO. 209 records from Nannofossil abundance of Hole 55-433. 8 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 702 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 8 records from Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species. 36 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 688 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 4 records from Freshwater fish records via iRecord - additional species. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 23 records from Abundance of benthos infauna at station GIK23055-1. 3 records from A new species of phlebotomine sandfly, Pintomyia (Pifanomyia) duckei (Diptera: Psychodidae) from Manaus, State of Amazonas, Brazil. 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 13 records from Benthic macrofauna abundance of sediment core 13200-017. 126 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 6 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 551 records from Gunma Museum of Natural History, Fungi Specimen. 252 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 2 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 1845 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 2702 records from Plant specimens of Horaiji-san Museum of Natural History Kichi T. collection. 1 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 2 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 102 records from Organochlorine and total mercury in bivalve Anadara tuberculosa and other species from the Nicoya Gulf, Costa Rica in 1988. 3720 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 46 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 103128 records from UWFC Ichthyology Collection. 279 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 591 records from Auburn University Museum of Natural History Invertebrates. 3 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 188 records from The ultor - group of the genus Dolichogenidea Viereck (Hymenoptera, Braconidae, Microgastrinae) from China with the descriptions of thirty-nine new species. 987 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 4 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 15862 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 544 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 20 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 15476 records from CUMV Fish Collection. 2107 records from MUST, Insecta. 112 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 243450 records from Données ONF faune-flore-fonge. 582 records from Collection entomologique Pierre Lachiver. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 1 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 14 records from Stenus maculifer CAMERON: eine Büchse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 16756 records from University of Tennessee Fungal Herbarium. 1067 records from University of Michigan Museum of Zoology, Division of Mollusks. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 1529 records from Flora ficológica de la huasteca potosina. 370 records from Range table from benthic foraminifers in ODP Hole 144-874B. 56 records from Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 65 records from Type Specimen Database of Museum and Institute of Zoology PAS. 57457 records from DASSH Data Archive Centre Academic Surveys. 1359 records from Herbier de Wallis et Futuna. 6 records from Annotated type-catalogue of Brachyura (Crustacea, Decapoda) of the Muséum national d’Histoire naturelle, Paris. Part II. Gecarcinidae and Grapsidae (Thoracotremata, Grapsoidea), with an Appendix of pre- 1900 collectors. 16 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 1 records from A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile. 43 records from Coleccion de helechos de la FML. 35 records from Quoll sightings register for Nth QLD. 3 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 16 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 41841 records from University of Florida Invertebrate Paleontology. 15 records from Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae). 699 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 608 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 9 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 96 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362. 6974 records from Inventaire des Ephémères de métropole (Opie). 65 records from Tetrápodos de Uruguay. 188 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 9 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 21 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 13 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 20 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 1508 records from University of Kentucky Insect Collection. 45487 records from Atlas des Orthoptères et Mantides de France métropolitaine. 41 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 257 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 12794 records from UAM Bird Collection (Arctos). 2 records from A new species of Eremias (Squamata: Lacertidae) from the arid mountains of Pakistan. 24 records from Ostracoda abundance of Hole 48-406. 24 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 425 records from UTEP Herpetology Osteology (Arctos). 2072 records from Vertical distribution of meiofauna in the North Sea and the Westerschelde estuary in 1993 and 1994. 10811 records from The Scottish Squirrel Database. 16 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 2 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 6 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 1 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 1 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 1 records from Collection Crustacea - KAUMM. 2256 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 203 records from FBIP: Baboon spider distribution records from selected South African museums. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 22 records from Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 16 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 20 records from Coccolith counts of multinet SO119_MSN1301. 1 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 81 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 7 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 3 records from Three new species of moth flies (Diptera, Psychodidae, Psychodinae) from the Afrotropical Region. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 116 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 1482 records from Nannofossil abundance of Hole 94-607. 1007 records from Thrips (Thysanoptera) in Norway. 64 records from Mammalian Specimens of the Yamagata Prefectural Museum. 33 records from BID-Malawi-Arctiidae-Biodiversity-Data. 20 records from Bird specimens of Ryukyu University Museum (Fujukan). 1134 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 23 records from Weevils of Poland. 2 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1171 records from Arachnida of Costa Rica (INBio). 2342 records from Ross A. Layberry, Collection. 42 records from Occurrence of some antimalarial plants from Cameroon. 23 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 1308 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 219 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 119 records from Microfossil abundance of Hole 50-416A. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 1 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 1 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 254 records from Pollen analysis of sediment profile BLA00 from Blankensee. 30 records from Collection Crustacea - ZSRO. 700 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 1662 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 1101 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 2 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 1576 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 173 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 4 records from Four new species of the genus Diaphorus (Diptera: Dolichopodidae) from China. 3 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 97 records from Données coléoptères de l'Association des Entomologistes de Picardie. 2016 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 17 records from A revision of Japanese Torymus Dalman (Hymenoptera: Torymidae). 125 records from Total foraminifera counts from multinet M31/2_MSN890. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 1018 records from CNAN/Araneae. 1 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 10093 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 505 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 20 records from Taxonomic review of the Hyphessobrycon panamensis species-group (Characiformes: Characidae). 527 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 1749 records from Benthic foraminifera abundance of Hole 84-570. 1091 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 2 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 27 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 2 records from A revision of Cinnadenia Kosterm. (Lauraceae). 2376 records from Colección de Zoología Invertebrados - Helmintología. 3520 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 159 records from Planktic foraminifera assemblage in sediment core SU90-I06. 89 records from Total foraminifera counts of multinet POS247/2_MSN1384. 3930 records from Fishes of INEP and NFH collections. 88061 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 13 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 20 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 5 records from The Resin and Carder bees of south India (Hymenoptera: Megachilidae: Anthidiini). 46 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 1 records from Four new genera of Schizopteridae (Hemiptera: Heteroptera) from theAfrotropical and Neotropical regions. 6 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 480 records from Magnoliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 40 records from Review of the mirine plant bug genus Eurystylus Stål fro
Keywords: GBIF; biodiversity; species occurrences